Correlation of Learning Style and Learning Motivation on Learning Outcomes Understanding Concepts - Setiasih, Muhti; Degeng, Made Duananda Kartika; Kurniawan, Citra (Universitas Negeri Malang, 2024)
The aim of this research is to determine the relationship between learning style and learning motivation with students' learning outcomes in understanding concepts in the Teaching and Learning course at the State University of Malang. This research was conducted using the Multiple Correlation Test simultaneously and the Pearson Correlation Test. From the results of data processing it is known that sig. (2-tailed) learning style and learning outcome variables are 0.084 and sig. (2-tailed) on the learning motivation and learning outcomes variables is 0.718. Meanwhile, the results of simultaneous multiple correlation analysis test data processing on sig. F Change is worth 0.219. The findings from this research indicate that there is no relationship between learning style and learning motivation and students' conceptual understanding in the Teaching and Learning course at the State University of Malang. This can be caused by several factors such as a less supportive learning environment, differences in educationa